2012
DOI: 10.1099/ijs.0.035709-0
|View full text |Cite
|
Sign up to set email alerts
|

Legionella steelei sp. nov., isolated from human respiratory specimens in California, USA, and South Australia

Abstract: Legionella -like bacteria were isolated from the respiratory tract of two patients in California, USA, and South Australia, but were not thought to cause disease. These bacteria, strains F2632 and IMVS-3376T, were found to have identical Legionella macrophage infectivity potentiator (mip) gene sequences and were therefore further characterized to determine their genetic and phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…This Legionella species grows robustly in amoebae but fails to multiply within macrophages, although the bacterium is not killed (Supplementary Figure S7), suggesting that L. steelei can also evade phagosome-lysosome fusion in macrophages. Similarly, Edelstein et al (2012) have previously shown Legionella protist grazers…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This Legionella species grows robustly in amoebae but fails to multiply within macrophages, although the bacterium is not killed (Supplementary Figure S7), suggesting that L. steelei can also evade phagosome-lysosome fusion in macrophages. Similarly, Edelstein et al (2012) have previously shown Legionella protist grazers…”
Section: Discussionsupporting
confidence: 52%
“…steelei was originally isolated from the respiratory tract of a patient in Australia (Edelstein et al, 2012). This Legionella species grows robustly in amoebae but fails to multiply within macrophages, although the bacterium is not killed (Supplementary Figure S7), suggesting that L. steelei can also evade phagosome-lysosome fusion in macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cluster is also closely related to L. tucsonensis and L. steelei (bootstrap values = 97–99%) , species isolated from humans after renal transplant and bronchitis infection, respectively (Thacker et al., ; Edelstein et al. ).…”
Section: Resultsmentioning
confidence: 84%
“…While L. pneumophila, Legionella steelei, Legionella dumoffii , and Legionella norrlandica are able to grow within A . castellanii , several other species including Legionella longbeachae, Legionella jordanis , and Legionella anisa are unable to do so (Neumeister et al, 1997 ; Edelstein et al, 2012 ; Rizzardi et al, 2014 ). Thus, the fate of both the bacterium and the host cell is greatly determined by the inherent properties of each organism.…”
Section: Factors Affecting the Outcome Of Legionella mentioning
confidence: 99%